Response of the ENPP1‐Deficient Skeletal Phenotype to Oral Phosphate Supplementation and/or Enzyme Replacement Therapy: Comparative Studies in Humans and Mice. (18th February 2021) - Ferreira, Carlos R; Kavanagh, Dillon; Oheim, Ralf; Zimmerman, Kristin; Stürznickel, Julian; Li, Xiaofeng; Stabach, Paul; Rettig, R Luke; Calderone, Logan; MacKichan, Colin; Wang, Aaron; Hutchinson, Hunter A; et al.
ABSTRACT: Inactivating mutations in human ecto‐nucleotide pyrophosphatase/phosphodiesterase‐1 (ENPP1) may result in early‐onset osteoporosis (EOOP) in haploinsufficiency and autosomal recessive hypophosphatemic rickets (ARHR2) in homozygous deficiency. ARHR2 patients are frequently treated with phosphate supplementation to ameliorate the rachitic phenotype, but elevating plasma phosphorus concentrations in ARHR2 patients may increase the risk of ectopic calcification without increasing bone mass. To assess the risks and efficacy of conventional ARHR2 therapy, we performed comprehensive evaluations of ARHR2 patients at two academic medical centers and compared their skeletal and renal phenotypes with ENPP1‐deficient Enpp1 asj/asj mice on an acceleration diet containing high phosphate treated with recombinant murine Enpp1‐Fc. ARHR2 patients treated with conventional therapy demonstrated improvements in rickets, but all adults and one adolescent analyzed continued to exhibit low bone mineral density (BMD). In addition, conventional therapy was associated with the development of medullary nephrocalcinosis in half of the treated patients. Similar to Enpp1 asj/asj mice on normal chow and to patients with mono‐ and biallelic ENPP1 mutations, 5‐week‐old Enpp1 asj/asj mice on the high‐phosphate diet exhibited lower trabecular bone mass, reduced cortical bone mass, and greater bone fragility. Treating the Enpp1 asj/asj mice with recombinant Enpp1‐Fc protein between weeks 2 and 5 normalized trabecular bone mass, normalized or improved bone biomechanical properties, and prevented the development of nephrocalcinosis and renal failure. The data suggest that conventional ARHR2 therapy does not address low BMD inherent in ENPP1 deficiency, and that ENPP1 enzyme replacement may be effective for correcting low bone mass in ARHR2 patients without increasing the risk of nephrocalcinosis. © 2021 American Society for Bone and Mineral Research (ASBMR).